Pemikiran Tasawuf Muh Arsyad al-Banjari dan Pengaruhnya di Masyarakat Kalimantan Selatan - Maimunah Zarkasyi (Islamica: Jurnal Studi Keislaman, 2008)
Muhammad Arsyad al-Banjari is hitherto known in the Malay world as a jurist of Shafi?i school of thought. Little has been known concerning his Sufi inclination and ideas. This paper is interested in investigating just that. By scrolling on his works and exploring the genealogy of his thought, this paper is interested in unraveling the Sufistic tendency that manifests in the thought of al-Banjari. The premise that underlies this paper is that the thought of al-Banjari on Sufism is deep-rooted in the 18th century Sufistic current of thought in Mekka. This current of thought is characterized by its persistence to reconcile Shari?ah and Tasawuf. Zakariyah al-Anshari was regarded as its foremost leader. He was of an Egyptian origin and wrote a book entitled Fath al-Rahman. Many of al-Banjari?s works including Kanz al-Ma?rifah that he wrote in the Javanese Arabic may be seen as both an annotation and commentary on Fath al-Rahman. A careful analysis on their works reveals an unmistakable intellectual link between the two. Both have worked within the perspective of Syari?ah and Tasawuf and are mainly interested in reconciling them. To their view, it is only by reconciling Syari?ah and Tasawuf that we may have a clear idea concerning the way (Shari?ah), the order (Tariqah) and the truth (Haqiqah) and the relationship between them. By virtue of his concern in integrating Syari?ah and Tasawuf, al-Banjari is known both as a jurist and a Sunni Sufi. He was also responsible for transferring the knowledge of Tasawuf and Jurisprudence from their authoritative sources in the Middle East to the people of Southern Kalimantan. His intellectual and social role has brought about a significance change in the social fabric of his society. It was in his hand that the inventive practices (bid?ah) and the religious mischief found in his society were finally eliminated and brushed away. This paper will explore these aspects of al-Banjari?s Sufism.